A multicentre randomized trial of the treatment of patients with pemphigus vulgaris with infliximab and prednisone compared with prednisone alone. (1st March 2015) - Hall, R.P.; Fairley, J.; Woodley, D.; Werth, V.P.; Hannah, D.; Streilein, R.D.; McKillip, J.; Okawa, J.; Rose, M.; Keyes‐Elstein, L.L.; Pinckney, A.; Overington, A.; et al.
Summary: Background: Pemphigus vulgaris (PV) is a blistering disease and tumour necrosis factor‐α has a role in its pathogenesis. Objectives: To evaluate the safety of infliximab (IFX) with prednisone compared with prednisone alone in the treatment of PV. In addition, treatment response was assessed and mechanistic studies were performed. Methods: Subjects with PV who had ongoing disease activity while being maintained on prednisone were randomized to receive either IFX or placebo in addition to prednisone. Response status and immunoglobulin (Ig) G anti‐desmoglein (Dsg)1 and Dsg3 antibodies were assessed at 18 and 26 weeks. Results: Ten subjects were randomized to each group. There were no safety signals during the course of the study. At week 18, one subject in each group had responded. At week 26, three IFX‐treated subjects vs. none in the placebo group had responded ( P = 0·21). At weeks 18 and 26, the median IgG anti‐Dsg1 and anti‐Dsg3 levels were lower in the IFX‐treated patients [IgG anti‐Dsg‐1 (week 18, P = 0·035; week 26, P = 0·022); IgG anti‐Dsg3 (week 18, P = 0·035; week, 26 P = 0·05)]. Conclusions: This study is limited by the relatively small sample size. There was no significant difference between study arms in the proportion of subjects with treatment‐related adverse events > grade 3. IFX therapy was not shown to be effective for the treatment of patients with PV in this randomized, placebo‐controlled trial, although IFX treatment may be associated with a decrease in anti‐Dsg1 and Dsg3 antibodies.